641. Activity of Gepotidacin Tested Against Molecularly Characterized Escherichia coli Isolates Resistant to Commonly Used Oral Therapies for UTI in the US (2019-2020). (15th December 2022) - Mendes, Rodrigo E; Ryan Arends, S J; Kimbrough, John H; Kantro, Valerie; Butler, Deborah; Scangarella-Oman, Nicole E; Streit, Jennifer M; Castanheira, Mariana
Abstract: Background: Gepotidacin is a novel first in class triazaacenaphthylene antibiotic in Phase 3 clinical trials for the treatment of gonorrhea and uncomplicated urinary tract infection (UTI). This study evaluates the epidemiology of E. coli (EC) causing UTI in US patients and the activity of gepotidacin and comparators against various subsets, including those with characterized resistance mechanisms. Methods: 1, 993 EC collected from 45 US sites were included as part of the Gepotidacin UTI Global Surveillance Study as part of the SENTRY Antimicrobial Surveillance Program (2019-2020). Isolates were tested for susceptibility (S) by CLSI methods and CLSI interpretations were applied. Isolates that met MIC criteria for screening of extended-spectrum β-lactamase (ESBL) genes were subjected to genome sequencing followed by ESBL gene screening and epidemiology typing (MLST, O:H, and fimH ). Results: A total of 84.4% (1, 682/1, 993) EC were ESBL negative (Table). Among these isolates, 16.5% (278/1, 682) were not S to the fluoroquinolones (FQ) ciprofloxacin and/or levofloxacin, whereas 26.2% (440/1, 682) were not S to trimethoprim-sulfamethoxazole (SXT). An ESBL phenotype was noted in 15.6% (311/1, 993) of EC, which tended to be mostly not S to the FQs (79.7%), SXT (61.7%), amoxicillin-clavulanate (52.9%), and oral cephalosporins (99.7%). Most ESBL isolates carried CTX-M alleles alone (81.4%; 253/311), whereas 9.6% (30/311) had plasmid AmpC genes. Approximately half (56.3%; 175/311) of ESBL isolates belonged to clonal complex (CC) 131, of which 70.9% (124/175) were O25b:H4 and carried fimH 30. Overall, gepotidacin had MIC90 of 2-4 mg/L against various phenotypic/genotypic subsets. Conclusion: High rates of EC not S to commonly used oral agents (FQs and SXT) were observed. ESBL phenotype further compromised the activity of oral agents, including oral cephalosporins. Gepotidacin had potent and stable in vitro activity against various subsets, including the resistant CC131 O25b:H4 clone. These data support the further clinical development of gepotidacin as a treatment option for UTI caused by EC, including resistant isolates against which other oral treatment options are limited. Disclosures: Rodrigo E. Mendes, PhD, AbbVie: Grant/Research Support|Cidara: Grant/Research Support|GSK: Grant/Research Support|Melinta: Grant/Research Support|Nabriva Therapeutics: Grant/Research Support|Office for Assistant Secretary of Defense for Health Affairs: Grant/Research Support|Pfizer: Grant/Research Support|Shionogi: Grant/Research Support|Spero Therapeutics: Grant/Research Support SJ Ryan Arends, PhD, AbbVie: Grant/Research Support|GSK: Grant/Research Support|Nabriva Therapeutics: Grant/Research Support|Shionogi: Grant/Research Support John H. Kimbrough, PhD, AbbVie: Grant/Research Support|GSK: Grant/Research Support Valerie Kantro, BA, AbbVie: Grant/Research Support|GSK: Grant/Research Support|Melinta: Grant/Research Support|Shionogi: Grant/Research Support Nicole E. Scangarella-Oman, MS, GlaxoSmithKline plc.: Employee and shareholder Jennifer M. Streit, BS, MT(ASCP), Cidara: Grant/Research Support|GSK: Grant/Research Support|Melinta: Grant/Research Support|Shionogi: Grant/Research Support Mariana Castanheira, PhD, AbbVie: Grant/Research Support|Cidara: Grant/Research Support|GSK: Grant/Research Support|Melinta: Grant/Research Support|Pfizer: Grant/Research Support|Shionogi: Grant/Research Support.